TMIC-19. H+ EXTRUSION PROTEIN NA/H EXCHANGER IN METABOLIC POLARIZATION OF GLIOMA-ASSOCIATED MICROGLIA/MACROPHAGES AND TUMOR IMMUNITY. (11th November 2019) - Nabiul Hasan, Md; Guan, Xiudong; Ahuja, Avani; Castro, Maria; Kohanbash, Gary; Sun, Dandan
Abstract: Immunosuppressive tumor microenvironment (TME) in glioblastoma (GBM) attributes to poor efficacy of chemotherapy and/or immunotherapy. We recently reported that SLC9A1 gene expression (Na/H exchanger 1, NHE1) in GBM tumor correlates with increased macrophage tumor infiltration and worsened patient survival. Temozolomide (TMZ) monotherapy, the standard care therapy for GBM, stimulates NHE1 protein expression in mouse syngeneic glioma models. We speculate that in response to TMZ therapy, NHE1 promotes immunosuppressive TME development via deregulation of glucose metabolism and anti-tumor function of immune cells. CD57BL/6 mice bearing GL26 glioma tumor were treated with NHE1 inhibitor HOE-642 (H, 0.3 mg/kg/day), TMZ (T, 2.5 mg/kg/day), and/or anti-PD-1 (10 mg/kg/day) monotherapy or in combination. The T+H+anti-PD-1 combination therapy increased glucose uptake (2-NBDG) and mitochondrial mass (mitotracker fluorescent intensity) of tumor infiltrating CD8 + T-cells by 2-fold compared to the monotherapies. This suggests that NHE1 protein is involved in metabolic transformation of T-cells and affects their responses to chemo and/or immunotherapy. Furthermore, we detected that specific deletion of Nhe1 in Cx3Cr1 CreErT 2 r+/ - ;Nhe1 f/f mice ( Nhe1 KO) alters activation of glioma-associated microglia/macrophages (GAM) and T-cells in response to TMZ therapy. TMZ monotherapy stimulated macrophage (CD11b + CD45 hi ) infiltration by 2.5-fold in Cx3Cr1 CreErT 2 -/ - ;Nhe1 f/f ( Nhe1 Con) mice bearing SB28-GFP glioma tumor with abundant proinflammatory CD16/32 + GAMs. In contrast, TMZ treated Nhe1 KO mice displayed 3-fold reduction in tumor infiltrating GAMs with nearly abolished Ym-1 + tolerogenic macrophages, 3-fold reduction of tumor-promoting CD4 + CD25 + FoxP3 + regulatory T-cells (Treg) and increased CD8 + /Treg ratio by 2-fold than the Nhe1 Con mice. Importantly, TMZ followed by anti-PD-1 therapy prolonged survival of Nhe1 KO mice but not Nhe1 Con mice. Taken together, our study suggests that NHE1 is involved in transformation of GAMs and PD-1 check point activation of T-cells. Blocking NHE1 function in combination with TMZ and anti-PD-1 may restore glucose metabolism of immune cells necessary for their anti-tumor function.